2019
DOI: 10.1186/s12874-019-0841-6
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of an algorithm based on medico-administrative data to identify hospitalized patients with major bleeding presenting to an emergency department

Abstract: Background Validation studies on an ICD-10-based algorithm to identify major bleeding events are scarce, and mostly focused on positive predictive values. Objective To evaluate the sensitivity and specificity of an ICD-10-based algorithm in adult patients referred to hospital. Methods This was a cross-sectional, retrospective analysis. Among all hospital stays of adult pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Table S1 shows the ICD‐10 (International Statistical Classification of Diseases and Related Health Problems 10th Revision) codes that were utilized to identify the primary and secondary outcomes. Diagnostic accuracy of major bleeding and death ICD‐10 algorithms were assessed in a couple of validation studies with mixed results 27,28 . Studies that assessed the validity of ICD‐10 algorithms of other outcomes were not identified in the published literature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table S1 shows the ICD‐10 (International Statistical Classification of Diseases and Related Health Problems 10th Revision) codes that were utilized to identify the primary and secondary outcomes. Diagnostic accuracy of major bleeding and death ICD‐10 algorithms were assessed in a couple of validation studies with mixed results 27,28 . Studies that assessed the validity of ICD‐10 algorithms of other outcomes were not identified in the published literature.…”
Section: Methodsmentioning
confidence: 99%
“…Diagnostic accuracy of major bleeding and death ICD-10 algorithms were assessed in a couple of validation studies with mixed results. 27,28 Studies that assessed the validity of ICD-10 algorithms of other outcomes were not identified in the published literature.…”
Section: Icd-10 (International Statistical Classification Of Diseasesmentioning
confidence: 99%
“…This observation was confirmed in the present study for all antiplatelet drugs, in monotherapy or dual therapy, but with overall lower incidence rates. This could be explained by the strict definition of the severity of major bleeding used in our study and by the systematic medical validation of all events [23].…”
Section: Plos Onementioning
confidence: 99%
“…All bleeding events were medically validated using pre-specified criteria which were somewhat consistent with the "severe or life-threatening' item from GUSTO. The systematic medical validation of all bleeding limited the overestimation of incidence rates of major bleeding [23]. Exposure in our study was based on reimbursement claims data.…”
Section: Plos Onementioning
confidence: 99%
“…A pilot study found good sensitivity for the computer search. 33 In each area, a referent expert medical doctor checked all records identified for oral anticoagulant exposure and severe bleeding criteria (see below for details).…”
Section: What This Study Addsmentioning
confidence: 99%